TEACHING WRITING RECOUNT TEXT USING STUDENT TEAM ACHIEVEMENT DIVISION - Citra Ayu Nisa; Sri Supiah Cahyati (PROJECT (Professional Journal of English Education), 2024)
This research was aimed to identify (1) the implementation of teaching writing recount text using STAD technique, (2) the response of the teacher and students toward the implementation of scenario in teaching writing recount text using STAD technique, and (3) the difficulties faced by the students in writing recount text using STAD technique. This research was conducted by using descriptive qualitative method. The subject of the research were students grade X MIPA 3 of SMAN 1 Cipatat. It consisted of one class with 36 students as respondents. The instruments of this research were document analysis, observation, questionnaire, and interview. The data were analyzed using Miles and Hubbermans (1994) concept of qualitative data analysis. Based on the document analysis, observation, questionnaire, and interview, it was found that teaching-learning process ran well. Students were engaged, excited, and motivated to write. Additionally, students gave positively response that the students felt that STAD technique was interesting for learning because it was easy to understand, and made class was fun, and classroom atmosphere became different used this technique. However, the data from the questionnaire showed that some students have difficulty translating text in English, it is caused by the lack of vocabulary. The result of the research showed that STAD technique could significantly improve students in writing recount text.